2022
DOI: 10.1111/pcn.13510
|View full text |Cite
|
Sign up to set email alerts
|

YY1 (Yin‐Yang 1), a transcription factor regulating systemic inflammation, is involved in cognitive impairment of depression

Abstract: Aim: Clinical and preclinical studies suggest that alterations in the peripheral and brain immune system are associated with the pathophysiology of depression, also leading to changes in local glucose metabolism in the brain. Here, the authors identified Yin-Yang 1 (YY1), a transcription factor closely associated with central and peripheral inflammation.Methods: Plasma levels of YY1, interleukin (IL) 6, and IL-1β in major depressive disorder (MDD) were collected before and after treatment with vortioxetine, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 61 publications
(113 reference statements)
0
5
0
Order By: Relevance
“…It is accompanied by a decrease in SIRT6 levels and an increase in YY1 levels in aged mice [14]. Data from clinical studies indicate that plasma levels of YY1 are significantly elevated in patients with major depressive disorder [28]. Notably, in a previous study, using chromatin immunoprecipitation, we showed that YY1 may be recruited by nuclear-translocated PAC1-R [21].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…It is accompanied by a decrease in SIRT6 levels and an increase in YY1 levels in aged mice [14]. Data from clinical studies indicate that plasma levels of YY1 are significantly elevated in patients with major depressive disorder [28]. Notably, in a previous study, using chromatin immunoprecipitation, we showed that YY1 may be recruited by nuclear-translocated PAC1-R [21].…”
Section: Discussionmentioning
confidence: 65%
“…It should be mentioned that the result of the Western blot analysis showed that the effect of 0.1 µmol/kg/day SPAM1 was more significant than that of 100 µmol/kg/day SPAM1. In fact, the positive allosteric modulation site of PAC1-R may be able to detect some type of stress metabolites, such as PACAP (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), which is a natural metabolite of the stress hormone PACAP38. The working mechanism of SPAM1 involves the imitation (mimicry) of some type of stress metabolites, such as PACAP (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), to trigger self-defensive responses in the nervous system, including anti-senescence, neuroprotection, and nerve regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…[ 61 , 76 , 77 ] Similarly, human YY1 has been reported to participate in cancer development, modulation of neuroinflammation, and Th17 cell differentiation. [ 61 , 78 , 79 ] To further explore the translatability between human and mouse YY1, we compared both YY1 protein sequences on the UniProt website. The result showed that they shared high degree of homology (>98%), suggesting that our findings in mouse YY1 were largely representative of human YY1.…”
Section: Discussionmentioning
confidence: 99%
“…YY1 is correlated with cognitive impairment seen in depression. 38 Moreover, astrocytic YY1 plays an essential role in normal brain development, locomotor activity, motor coordination, and cognition. 39 After downregulating YY1, the disorders of learning and memory of SAE mice with USP8 overexpression were exacerbated, and behavioural deficits were aggravated.…”
Section: Discussionmentioning
confidence: 99%
“…YY1 is correlated with cognitive impairment seen in depression 38 . Moreover, astrocytic YY1 plays an essential role in normal brain development, locomotor activity, motor coordination, and cognition 39 .…”
Section: Discussionmentioning
confidence: 99%